Analisis Kesiapan Pensiun Pekerja Biasa di Jabodetabek dan Tantangan Industri Dana Pensiun di Indonesia (Jurnal Inovasi Manajemen, Kewirausahaan, Bisnis dan Digital, 2025)
This study aims to map the level of retirement readiness among ordinary workers in Greater Jakarta and the challenges facing the pension fund industry in Indonesia using a mixed quantitative and qualitative method involving 100 workers. The study concludes that the retirement readiness of ordinary workers in Jabodetabek is relatively low, with 55% of workers unsure whether they can cover their living expenses in old age due to their current income being considered insufficient and a lack of understanding of the living expenses required during retirement. Awareness of retirement is reflected in 97% of workers willing to set aside part of their salary for retirement due to fear of poverty in old age, with 59% of workers able to set aside contributions ranging from IDR 100,000 to IDR 500,000 per month for pension funds. Only 18% of workers have a clear preference to fully enjoy their retirement, while 47% of workers want to start a small business, and 24% of workers are unsure about what their retirement will look like. The majority, or 41% of workers, have financial products in the form of savings accounts at banks, and 39% have other financial products, while only 8% have retirement funds. Only 18% of workers have a clear preference for enjoying their retirement, while 47% want to start a small business and 24% are unsure about what their retirement will look like. The majority, or 41%, of workers have financial products in the form of savings accounts at banks, and 39% have other financial products, while only 8% have pension funds. The challenges facing the pension fund industry in Indonesia are centered on 1) low participation rates, 2) financial literacy and awareness, 3) investment performance, 4) digital access, 5) inconsistencies in the pension system, and 6) demographic and longevity risks. The pension fund industry is required to develop flexible and affordable products. Massive education, digital access availability, and inclusive policies are key to preparing workers for retirement and preventing poverty in old age. This study recommends synergy between the government, industry players, and educational institutions to improve retirement literacy and participation. Increased incentives for participants and integration of the national pension system are also needed to create a more prosperous and sustainable retirement.